Validasi skor Coagulopathy of Severe Trauma (COAST) dalam memprediksi Acute Trauma Coagulopathy (ATC) di Rumah Sakit Umum Pusat Sanglah Denpasar - Putu Chandra Wibawa; I Gede Suwedagatha; I Wayan Niryana (Intisari Sains Medis, 2022)
Introduction: The Coagulopathy of Severe Trauma (COAST) score is a scoring system that predicts the clinical condition of ATC. The COAST score has a high specificity of 96% and a sensitivity of 80% at a cut-oﬀ 3, which can accurately predict coagulopathy and has a significant outcome. This study tested the validity of the Coagulopathy of Severe Trauma (COAST) scoring in predicting Acute Traumatic Coagulopathy (ATC) at the Sanglah Central General Hospital (RSUP) Denpasar. Method: Observational study with diagnostic test and cross-sectional design carried out from December 1, 2020 to February 28, 2021. Patients suspected of ATC are patients who present with a history of trauma with an increase of two out of three, namely, Prothrombin Time (PT) >18 seconds, Activated Partial Thromboplastin Time (aPTT) >36 seconds, and International Normalized Ratio (INR) >1.6. Samples were excluded if they refused to participate in the study, had severe head injury, concomitant severe systemic disease, had blood clotting disorders or were taking blood thinning drugs, burn patients, and pregnant patients. The COAST score was assessed based on the components of the trapped assessment, blood pressure, temperature, chest decompression, and abdominal/pelvic injury. COAST scores were analyzed using ROC curves and diagnostic tests, as well as logistic regression tests. The value of p <0.05 indicates a significant result. Results: This study involved 60 patients with 10 ATC positive patients and the remaining 50 ATC negative. Significant differences (p<0.05) on the incidence of ATC were found in the variables of age, ISS score, trapped, chest decompression, abdominal/pelvic injury, systolic blood pressure, PT, aPTT, INR, and COAST score. ROC curve analysis showed a COAST score with a cut-off value of 2.5 (60% sensitivity; 88% specificity; p=0.01; 95% CI 0.555-0.965). The results of the diagnostic test cut-off score of 2.5 COAST scores with an OR of 11.00 (p=0.003; 95% CI 2.392-50.589). Multivariate analysis of COAST scores with the incidence of ATC showed a significant relationship (p=0.002). Conclusion: The COAST score is a valid scoring system to predict ATC at Sanglah Hospital Denpasar with a good level of sensitivity and specificity, with a cut off of 2.5.   Pendahuluan: Skor Coagulopathy of Severe Trauma (COAST) merupakan sistem skor yang memprediksi kondisi klinis ATC. Skor COAST memiliki spesifisitas tinggi 96% dan sensitifitas 80% pada cut-oﬀ ≥3, yang dapat secara tepat memprediksi koagulopati dan memiliki hasil yang secara signifikan. Penelitian ini menguji validitas skoring Coagulopathy of Severe Trauma (COAST) dalam memprediksi Acute Traumatic Coagulopathy (ATC) di Rumah Sakit Umum Pusat (RSUP) Sanglah Denpasar. Metode: Studi observasional dengan uji diagnostik dan desain cross-sectional yang dilaksanakan mulai 1 Desember 2020 sampai 28 Februari 2021. Pasien terduga ATC adalah pasien yang datang dengan riwayat trauma dengan peningkatan dua dari tiga yaitu, Prothrombin Time (PT) >18 detik, Activated Partial Thromboplastin Time (aPTT) >36 detik, dan International Normalized Ratio (INR) >1,6. Sampel dieksklusi apabila menolak keikutsertaan dalam penelitian, mengalami cedera kepala berat, penyakit sistemik berat bersamaan, menderita gangguan pembekuan darah atau mengonsumsi obat pengencer darah, pasien luka bakar, dan pasien hamil. Skor COAST dinilai berdasarkan komponen penilaian terjebak, tekanan darah, suhu, dekompresi dada, dan abdomen/pelvis injuri. Skor COAST dianalisis dengan kurva ROC dan uji diagnostik, serta uji regresi logistik. Nilai p<0,05 menunjukan hasil bermakna. Hasil: Penelitian ini melibatkan 60 pasien dengan 10 pasien ATC positif dan 50 sisanya ATC negatif. Perbedaan signifikan (p<0,05) terhadap kejadian ATC didapatkan pada variabel usia, skor ISS, terjebak, dekompresi dada, abdomen/pelvis injuri, tekanan darah sistolik, PT, aPTT, INR, dan skor COAST. Analisis kurva ROC menunjukan skor COAST dengan nilai cut-off 2,5 (sensitivitas 60%; spesifisitas 88%; p=0,01; CI95% 0,555-0,965). Hasil uji diagnostik nilai cut-off 2,5 skor COAST dengan OR 11,00 (p=0,003; CI95% 2,392-50,589). Analisis multivariat skor COAST dengan kejadian ATC menunjukan hubungan signifikan (p=0.002). Kesimpulan: Skor COAST merupakan sistem skoring yang valid untuk memprediksi ATC di RSUP Sanglah Denpasar dengan tingkat sensitivitas dan spesifisitas yang baik, dengan cut off ≥2,5.